Life Cycle Cost Analysis (LCCA) in Road Organization Application in Supiori Regency of Papua Province - Menufandu, Fitriah; Setyawan, Ary; Yulianto, Budi (IPTEK Journal of Proceedings Series, 2017)
Road plays an important life in human life in the present and in the future. Road serves to connect one area to another. Good road condition can support land transportation, development, economy, and government can run smoothly, and vice versa. Many factors result in road damage so that service life of road is not as planned. The objective of research is to compare two roads: Aminweri-Yendoker Street constituting the road in Supiori Regency Biak-Korem-Supiori Street constituting the national road connecting Biak and Supiori Regencies. This research employed Pavement Condition Index (PCI) to assess road damage level and condition and Life Cycle Cost Analysis (LCCA) to determine the economic cost during the road’s service life. The result of assessment using PCI method showed medium PCI score of 51.6 for Regency road and 69.3 for National road. Using LCCA method, the most efficient road management to achieve the service life of the two roads can be determined.